Toward the development of dynamic innovation capabilities in a hospitality industry: A case study in glamping service provider - Priyono, Anjar; Binti Nordin, Siti Nurulhuda; Abdul Shukor, Syadiyah (Asian Management and Business Review, 2025)
This research aims to identify the elements of dynamic innovation capabilities for glamping, with the goal of overcoming challenges in producing service designs aligned with customer preferences. The parties involved in glamping service design are also difficult to identify, hindering the optimal product development process. This study employs a qualitative case study approach to explore how glamping operators respond to changes in consumer preferences. Data collection was conducted using various techniques – i.e., interviews, observations, and focus group discussions – to maintain validity, and a series of case study protocols were prepared to ensure reliability. The findings indicate that the case study firm must continuously acquire tangible and intangible resources to pursue innovation. Notably, innovation is a moving target that requires constant changes. Resources will determine organizational capabilities, which subsequently govern the feasible strategic options. Firms may have various strategic choices for pursuing innovation, but success is determined by their capabilities. In other words, capabilities constraint for strategy execution. As this research is exploratory and conducted within a single company, it has limited generalizability. Future research could follow up by testing the findings through surveys.